Sistem Akuntansi Manajemen Sebagai Pemediasi Pengaruhdesentralisasiterhadap Kinerja Manajerial (Studi pada Satuan Kerja Perangkat Daerah Kota Jayapura) - Rante, Andika (Fakultas Ekonomi Universitas Wisnuwardhana, 2014)
Abstract :Purpose of this study was to examine whether AccountingSystem Management (MAS) is able to mediate effect ofdecentralization on managerial performance. Study population iswork unit heads of Jayapura City with sample were 39 respondents.Analysisused in this study is Path Analysis. Results showeddecentralization affect on managerial performance and ManagementAccounting System (MAS) can mediate effect of decentralization onmanagerial performance.Keywords: decentralization, MAS and managerial performance